Paradoxical bone mineralisation in the twin to twin transfusion syndrome. Issue 7 (July 1990) - Bishop, N J; King, F J; Ward, P; Rennie, J M; Dixon, A K
Abstract : We report twin preterm infants with the twin to twin transfusion syndrome, exhibiting grossly different bone densities on chest radiographs. Photonabsorptiometry showed the polycythaemic twin was osteopenic and the anaemic twin osteosclerotic; bone mineral contents were 0.028 g/cm and 0.074 g/cm respectively (normal mean (SD) 0.041 (0.006) g/cm. We speculate that alterations in macrophage derived osteoclastic activity contribute to these previously unreported findings.